The Entanglements of Affect and Participation - Raudaskoski, Pirkko; Klemmensen, Charlotte Marie Bisgaard (Frontiers in Psychology, 2019)
The purpose of the article is to elaborate on the scholarly debate on affect. We consider the site of affect to be the activities of embodied, socioculturally and spatially situated participants: “Affective activity is a form of social practice” (Wetherell, 2015, p. 147). By studying affect as a social phenomenon, we treat affect as a social ontology. Social practices are constituted through participation in social interaction, which makes it possible to study affect empirically. Moreover, we suggest that to consider affect a social ontology connects affect to agency. We regard affect as a participants’ phenomenon where emotions and knowledge are not separated, i.e. as a social epistemology. To capture the complexity of affective activity, the study of situated participation requires video data. We collected data at a centre for persons with acquired brain injury (ABI), which highlights research ethics. The International Classification of Functioning, Disability and Health (ICF) framework defines participation as involvement in life situations. ICF focuses on two broader perspectives: the body and the individual in society. We turn ICF’s abstract societal perspective on participation to meaningful local accomplishments in lived social practices. Our focus is, in line with a critical social ontology in disability studies, on how-ability, the communicative abilities of the residents (Hughes, 2007). To get closer to life situations as they unfold, we analyse participation in its details as embodied actions during activities in the material environment of the centre. To conclude, we demonstrate a resident’s competent participation in an occupational therapy session through a fine-grained analysis of affective activity. Interaction, practices and phenomena are complex theoretical and practical issues. In the analysis of the encounters as complex multimodal and -sensorial situations, we use an extended version of Ethnomethodological Conversation Analysis (EMCA) that incorporates the body and material environment with the interconnectedness of interactional episodes. To do this, we enlarge the scope of analysis from the complexity of local occasions of affective activity to connections between consecutive affective entanglements. In the indicated work we draw on theoretical (lamination) and methodological (nexus analysis) suggestions in order to best pursue the sociocultural nature of situated interactions.